Marked eosinophilia due to intestinal strongyloidiasis in an immunocompetent patient - Rodrigo, K.M.D.J.; Premaratna, R.; Chandrasena, T.G.A.N.; de Silva, N.; de Silva, H.J. (Sri Lanka Medical Association, 2012)
Strongyloides stercoralis is unique among the intestinal nematodes in that it has a free-living cycle in warm and tropical climates in addition to a parasitic cycle in its human host. In immuno-competent hosts, this parasite is mostly confined to the intestinal tract. Infection may be asymptomatic or it may induce a wide variety of symptoms such as nausea, vomiting, abdominal pain, chronic diarrhea, loss of weight and pruritus of the perianal region caused by autoinfective larvae ('larva currens'). Although intestinal nematode infections are relatively common in Sri Lanka, infection with S. stercoralis is infrequently reported. Prevalence rates of S. stercoralis infection in Sri Lanka range from 0-1.6% [1,2,3]. Here we report a case of symptomatic intestinal strongyloidiasis with marked eosinophilia.
Indexed in MEDLINE